2015
DOI: 10.3389/fbioe.2015.00014
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cell Cycle Proteins in Breast Cancer Cells with siRNA by Using Lipid-Substituted Polyethylenimines

Abstract: The cell cycle proteins are key regulators of cell cycle progression whose deregulation is one of the causes of breast cancer. RNA interference (RNAi) is an endogenous mechanism to regulate gene expression and it could serve as the basis of regulating aberrant proteins including cell cycle proteins. Since the delivery of small interfering RNA (siRNA) is a main barrier for implementation of RNAi therapy, we explored the potential of a non-viral delivery system, 2.0 kDa polyethylenimines substituted with linolei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…OlapModule 1 was enriched for DNA replication and nucleotide binding, while olapModule 2 was enriched in cell division. The deregulation of cell cycle progression is one of the causes of breast cancer (22). It was previously demonstrated that cell cycle abnormalities in G1/S or G2/M phases are frequently observed in breast cancer (24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OlapModule 1 was enriched for DNA replication and nucleotide binding, while olapModule 2 was enriched in cell division. The deregulation of cell cycle progression is one of the causes of breast cancer (22). It was previously demonstrated that cell cycle abnormalities in G1/S or G2/M phases are frequently observed in breast cancer (24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…Kaplan-Meier survival analysis was performed according to the survival time of patients in each class, to assess the significance of the effect of each module on survival time. The difference between the survival times of the two classes was compared with a log-rank test (22). P<0.05 was considered to represent a statistically significant difference.…”
Section: Identification Of Breastmentioning
confidence: 99%
“…Treated cells were then incubated for another 48 hr, before the final evaluation of cell growth by 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT) (Sigma‐Aldrich, St. Louis, MO) assay. To ensure the efficiency of siRNA silencing using the selected delivery system, CDC20 silencing siRNA (Cat # HSC.RNAI.N001255.12.1, IDT) was used as positive control, which was the most powerful siRNA we identified from a siRNA library against cell cycle proteins . In addition, we used 2 scrambled siRNAs as negative controls in our screens.…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers used TNFα gene as a target for the treatment of inflammatory and autoimmune diseases [52][53][54]. Murine models are the most popular animal models among various studies that used dsiRNA in vivo [47][48][49][50][51][52][53][54]; however, there are studies where other animal models, for example, rats, were used [53,55]. An exciting example of dsiRNA application was described by Doré-Savard and his colleagues, who demonstrated, for the first time, the efficient suppression of target genes in central nervous system (CNS) of rats by dsiRNA [55].…”
Section: Dicer Substrate Interfering Rnasmentioning
confidence: 99%
“…Several studies use dsiRNA to silence therapeutically relevant genes in vivo (Table 1). Frequently, cancer-related genes and genes of viruses [50,51,[56][57][58][59] are chosen as targets for dsiRNAs [47][48][49]. Several researchers used TNFα gene as a target for the treatment of inflammatory and autoimmune diseases [52][53][54].…”
Section: Dicer Substrate Interfering Rnasmentioning
confidence: 99%